Successful Paranoia: Friedrich Kittler, Lacanian Psychoanalysis, and the History of Science. (January 2019) - Schmidgen, Henning
With studies like Discourse Networks 1800/1900 and Gramophone, Film, Typewriter, Friedrich A. Kittler contributed significantly to transforming the history of media into a vital field of inquiry. This essay undertakes to more precisely characterize Kittler's historiographical approach. When we look back on his early contributions to studies of the relationship between literature, madness and truth – among others, his doctoral dissertation on the Swiss poet and writer Conrad Ferdinand Meyer – what strikes us is the significance that Jacques Lacan's structuralist psychoanalysis had in shaping the orientation of Kittler's later studies. His intensive engagement with Lacan galvanized Kittler's concern with the question of sex and/or gender in the evolution of the humanities as well as his concern with the media history of the university. At the same time, Kittler's reliance on Lacan led him to a kind of history that is interested above all in the internal logic of discourse. As we see, for instance, in Kittler's anecdotic treatment of 19th-century physiologist Hermann von Helmholtz, this historiography does not involve any original research in archives and/or museums. Rather, it builds upon existing historical accounts and focuses its analyses on the issue of symbolic structures. Instead of investigating the history of the material culture of science and technology, what is thereby ultimately reinforced is a philosophical idealism in which knowledge and paranoia become superimposed in and by means of an 'original syntax' (Lacan).